2021
DOI: 10.1007/978-3-030-70852-8_2
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Triggering of Android Memory Dumps for Stealthy Attack Investigation

Abstract: Attackers regularly target Android phones and come up with new ways to bypass detection mechanisms to achieve long-term stealth on a victim’s phone. One way attackers do this is by leveraging critical benign app functionality to carry out specific attacks.In this paper, we present a novel generalised framework, JIT-MF (Just-in-time Memory Forensics), which aims to address the problem of timely collection of short-lived evidence in volatile memory to solve the stealthiest of Android attacks. The main components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Performance overheads. The practical overheads recorded in the initial JIT-MF study (Bellizzi et al, 2021) were confirmed. With JIT-MF drivers enabled, only an average increase of 0.5s was registered in Pushbullet turnaround times for SMS operations, as observed from the web browser's Javascript console.…”
Section: Resultsmentioning
confidence: 70%
See 4 more Smart Citations
“…Performance overheads. The practical overheads recorded in the initial JIT-MF study (Bellizzi et al, 2021) were confirmed. With JIT-MF drivers enabled, only an average increase of 0.5s was registered in Pushbullet turnaround times for SMS operations, as observed from the web browser's Javascript console.…”
Section: Resultsmentioning
confidence: 70%
“…Therefore, any result- ing evidence has to be present in process memory, even if just briefly. While full-device static dumps of volatile memory typically require an unlocked bootloader and customized firmware, dynamic dumps of process memory do not necessarily face similar restrictions (Bellizzi et al, 2021). We show that this is the case when deployed using a mix of static and dynamic app instrumentation, at least when not involving system apps and services.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations